2021
DOI: 10.1055/s-0041-1723949
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns of Central Venous Catheter Placement and Confirmation in Pediatric Critical Care

Abstract: Optimal practices for the placement of central venous catheters (CVCs) in critically ill children are unclear. This study describes the clinical practice of pediatric critical care medicine (PCCM) providers regarding CVC placement, including site selection, confirmation practices and assessment of complications. Two-hundred fourteen PCCM providers responded to an electronic survey, including 170 (79%) attending physicians, 30 (14%) fellow physicians, and 14 (7%) advanced practice providers. PCCM providers most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…As much as 5.8% complications were observed, the main one being pneumothorax. The results show that the preferred CVC placement site was internal jugular, and the optimal position was superior vena cava-right atrium; similar data was obtained by Veten et al 1 On the other hand, Veten et al 1 mentioned a greater use of ultrasound guidance, unlike our operators who prefer to perform direct puncture: almost 70% used anatomical landmark.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…As much as 5.8% complications were observed, the main one being pneumothorax. The results show that the preferred CVC placement site was internal jugular, and the optimal position was superior vena cava-right atrium; similar data was obtained by Veten et al 1 On the other hand, Veten et al 1 mentioned a greater use of ultrasound guidance, unlike our operators who prefer to perform direct puncture: almost 70% used anatomical landmark.…”
supporting
confidence: 85%
“…All of this leads to wide variability in CVC placement practices. 1 Carmona et al reviewed the placement of 68 catheters in a Mexican hospital's pediatric service (48 through venipuncture and 20 through venesection), with 72% complications. 2 In a study performed in a Colombian university hospital, Rivera et al found that 100% of CVCs guided by real-time ultrasound were successful, compared with 87% of those conducted by anatomical landmarks.…”
mentioning
confidence: 99%
“…We thank Rodríguez-Campos, Falcon, and Carreazo for their interest in our article, reporting the practice patterns of central venous catheter (CVC) placement and confirmation in a pediatric critical care in North America, which showed wide practice variation in site selection, use of US guidance for insertion, and confirmation of CVC tip position among pediatric critical care providers. 1 Rodriguez-Campos et al pointed out a greater use of ultrasound (US) guidance among our respondents (90% for internal jugular [IJ] catheters), compared with their data (32%). The IJ was the most commonly cannulated site on their cohort, which is consistent with it being the preferred site among our respondents.…”
contrasting
confidence: 59%
“…Central venous catheter (CVC) placement facilitates life-saving interventions for critically ill children and is often performed by pediatric critical care medicine (PCCM) physicians. 1 As a result, the Accreditation Council for Graduate Medical Education (ACGME) requires that PCCM fellows develop the skills necessary for CVC placement prior to independent practice but does not dictate a minimum number of procedures. 2 Since procedural opportunities are increasingly rare during pediatric residency training, the development of CVC placement and other procedural skills among PCCM fellows must occur during fellowship.…”
Section: Introductionmentioning
confidence: 99%